2015
DOI: 10.1542/peds.2014-1798
|View full text |Cite
|
Sign up to set email alerts
|

Precollege and In-College Bullying Experiences and Health-Related Quality of Life Among College Students

Abstract: BACKGROUND AND OBJECTIVES: Bullying is a commonly occurring problem behavior in youths that could lead to long-term health effects. However, the impact of school bullying experiences on health-related quality of life (HRQOL) among college students has been relatively underexplored. This study aimed to describe school bullying experiences and to empirically examine their associations with HRQOL among college students in Taiwan.METHODS: Self-administered survey data (response rate 84.2%) were collected from 1452… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 35 publications
2
39
1
3
Order By: Relevance
“…It was in fact the most detrimental form of victimisation on HRQoL among girls. This finding is inconsistent with that of others [46]. Chen et al [46] investigated bullying occurring before and during college among 1452 college students in Taiwan, and found that when physical, relational and verbal bullying were taken into account, cyber bullying occurring before college was associated with better physical HRQoL but not psychological or social HRQoL.…”
Section: Discussionmentioning
confidence: 85%
“…It was in fact the most detrimental form of victimisation on HRQoL among girls. This finding is inconsistent with that of others [46]. Chen et al [46] investigated bullying occurring before and during college among 1452 college students in Taiwan, and found that when physical, relational and verbal bullying were taken into account, cyber bullying occurring before college was associated with better physical HRQoL but not psychological or social HRQoL.…”
Section: Discussionmentioning
confidence: 85%
“…Campus threat assessment is often presented as superior to unempirical safety approaches, like criminal profiling, intensified security measures, and faculty weapon accessibility (Randazzo & Cameron, 2012;Reddy et al, 2001;Sulkowski & Lazarus, 2011); but, the campus violence prevention field also includes heavilyresearched bullying, sexual assault, stalking, and intimate partner conflict findings that are likely applicable to targeted violence preclusion (Buhi et al, 2009;Chen & Huang, 2015;Fagan & Mazerolle, 2011;James et al, 2009). Administrators refusing to adopt "standard" campus threat assessment procedures have been described as "likely to be liable for negligence" and potentially "caus[ing] harm to student[s] or visitor[s] through…omissions" (Deisinger et al, 2014, p.114-115); however, with limited resources, these administrators must also inhibit intimate partner violence, sexual assault, stalking, and general crime concerns that are more common than targeted attacks (Buhi et al, 2009;Scalora et al, 2010;Thompson, Sitterle, Clay, & Kingree, 2007).…”
Section: The Remaining Goals Of Campus Threat Assessment Researchmentioning
confidence: 99%
“…Drug addiction is also considered among the factors associated with cyber bullying. Substance addiction and violence have been shown to be associated with both types of bullying and suicide attempt in high school students in the US [38,39].…”
Section: Alcohol-cigarette-substance Addictionmentioning
confidence: 99%